Unified Analysis of Thermodynamic and Rheological Properties of High Polymer Solutions : I. Binary Systems - Grigera, Tomás Sebastián (2002)
We present a comprehensive experimental study of thermodynamic and rheological properties of semidilute polymer solutions in good solvent. Osmotic pressure and viscosity measurements have been done in several polymer-solvent systems at different temperatures. A renormalization group technique was applied to analyze the data using de Gennes’s blobs model to connect dynamic and conformational quantities. The behavior of polymer systems in the whole range fromdilute to semidilute solutions can be satisfactorily described using only a fewnonuniversal quantities experimentally determined. An adequate agreement between experiments and theory was found, showing universal behavior with a system-dependent constant b that does not depend on molecular weight or concentration.